2021
DOI: 10.3390/nu13041327
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-Five-Year Trends in Dietary Patterns among Chinese Adults from 1991 to 2015

Abstract: Poor dietary habits have been shown to be associated with a range of chronic diseases and can potentially be a major contributor to non-communicable diseases (NCDs) mortality. We therefore aimed to identify the prevailing dietary patterns among Chinese adults and to evaluate trends in dietary patterns from 1991 to 2015. We used data collected in the China Health and Nutrition Survey (CHNS). Dietary patterns were identified using factor analysis of data from three consecutive 24 h dietary recalls. We studied 29… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
63
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 28 publications
2
63
0
Order By: Relevance
“…China is facing a Westernization of dietary patterns in a nutrition transition [ 16 ]. Individuals may have a similar change in dietary pattern over time, but they could have begun at a different level and changed at a different pace.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…China is facing a Westernization of dietary patterns in a nutrition transition [ 16 ]. Individuals may have a similar change in dietary pattern over time, but they could have begun at a different level and changed at a different pace.…”
Section: Discussionmentioning
confidence: 99%
“…The southern pattern represents a traditional dietary habit in southern China, where people are more likely to eat rice as a staple food with dishes [ 16 ]. Other studies also have reported the association between similar dietary patterns with overweight/obesity in the Chinese population [ 9 , 10 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The dietary pattern in China was relatively healthy in 2010 compared with that of other countries ( 40 ). However, China has since then quickly transformed toward unhealthy diets ( 40 ) under the increasing adoption of western dietary patterns ( 41 ). Such shifts are also related to changes in the food environment ( 11 ).…”
Section: Introductionmentioning
confidence: 99%